Allergy accelerates the disease progression of chronic rhinosinusitis. (2nd January 2019) - Shen, Keng-Chung; Lin, Yi-Tsen; Lin, Chih-Feng; Chang, Chin-Hao; Yeh, Te-Huei
Abstract: Background : The role of allergy in the development of chronic rhinosinusitis (CRS) in East Asians is not clear. Aims/objectives : The aim was to investigate the impact of allergies in the clinical characteristics of chronic rhinosinusitis. Material and methods : A total of 138 CRS patients who underwent endoscopic sinus surgery were included. A brief history of rhinosinusitis symptoms, blood eosinophil count, blood-specific allergen tests, computed tomography (CT) scan findings, Lund-Mackay (LM) CT scores, and Sino-Nasal Outcome Test (SNOT-22) Questionnaire scores, and sinoscopy findings at 3 and 6 months postoperatively. Results : The ImmunoCAP test was positive in 71(51%) patients and negative in 67(49%) patients. The mean age of those who received endoscopic sinus surgery was 7-years younger in the allergic group compared with the non-allergic group ( p = .008). The peripheral eosinophil count in the allergic group was higher than that of the non-allergic group ( p = .008). The LM scores and SNOT-22 scores were not significantly different between the two groups. The recurrence rate of nasal polyps in the allergic group was higher but without statistical significance. Conclusions and significance : Allergy may accelerate the disease progression of CRS. The presence of the serum-specific IgE was correlated with peripheral eosinophil percentage, especially in the CRSwNP patients.